2013
DOI: 10.7150/jca.6583
|View full text |Cite
|
Sign up to set email alerts
|

CBP Activity Mediates Effects of the Histone Deacetylase Inhibitor Butyrate on WNT Activity and Apoptosis in Colon Cancer Cells

Abstract: Mutations in the WNT/beta-catenin pathway are responsible for initiating the majority of colorectal cancers (CRCs). We have previously shown that hyperactivation of this signaling by histone deacetylase inhibitors (HDACis) such as butyrate, a fermentation product of dietary fiber, promotes CRC cell apoptosis. The extent of association between beta-catenin and the transcriptional coactivator CREB-binding protein (CBP) influences WNT/catenin signaling and, therefore, colonic cell physiology. CBP functions as a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
88
3
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(98 citation statements)
references
References 41 publications
6
88
3
1
Order By: Relevance
“…In a previous study 29, we demonstrated that ICG-001 treatment of HCT-116 and SW620 CRC cells diminished basal WNT/catenin activity and markedly repressed the hyperactivation of WNT signaling by butyrate. Further, while ICG-001 and butyrate inhibited proliferation in these cell lines, we demonstrated important cell type-specific effects of ICG-001/butyrate combinatorial treatment on CRC cell apoptosis.…”
Section: Resultsmentioning
confidence: 72%
See 3 more Smart Citations
“…In a previous study 29, we demonstrated that ICG-001 treatment of HCT-116 and SW620 CRC cells diminished basal WNT/catenin activity and markedly repressed the hyperactivation of WNT signaling by butyrate. Further, while ICG-001 and butyrate inhibited proliferation in these cell lines, we demonstrated important cell type-specific effects of ICG-001/butyrate combinatorial treatment on CRC cell apoptosis.…”
Section: Resultsmentioning
confidence: 72%
“…ICG-001, a specific inhibitor of CBP/beta-catenin association 23-28, influences butyrate-mediated WNT/catenin activity and colonic cell physiology 29. In a previous study 29, we demonstrated that ICG-001 treatment of HCT-116 and SW620 CRC cells diminished basal WNT/catenin activity and markedly repressed the hyperactivation of WNT signaling by butyrate.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…WNT signaling inhibitors have been identified and demonstrated therapeutic efficacy in various human cancers. [140][141][142][143][144][145][146][147][148][149] However, relatively little is known about clinically applicable WNT inhibitors for the treatment of GBM. In this section, we introduce a list of WNT signaling inhibitors that can be potentially used for anti-GBM therapy.…”
Section: Targeting the Wnt Signaling Pathway In Gbmmentioning
confidence: 99%